Heritage Resources and Teaching Approaches. A Study With Trainee Secondary Education History Teachers - Chaparro-Sainz, Álvaro; Felices-De la Fuente, María del Mar; Rodríguez-Medina, Jairo; Gómez-Carrasco, Cosme Jesús (Frontiers in Education, 2022)
At present, there is a great deal of research demonstrating the educational potential of heritage for the teaching of history. However, relevant studies have shown that, although it is a resource which is widely valued by teachers, its incorporation into the classroom remains limited. The aim of this study is to analyse the opinions of teachers in initial training regarding the use of heritage in the classrooms and to inquire about their relationship with their own teaching approaches, given that these may influence the use or evaluation they make of this resource. This study, which is non-experimental and quantitative in nature, has employed as a research tool a questionnaire with the participation of 646 students of the master’s degrees in Teacher Training in Geography and History of 22 different universities, representing 70% of the universities that offer this degree in Spain. The most significant results show a broad interest in heritage among future secondary education and baccalaureate level teachers, although there is a preference for heritage resources more linked to their undergraduate studies (History, History of Art, Archaeology) compared with heritage resources of a technological nature. Regarding teaching approaches, it has been observed that those who present a student-based approach (CCSF) value heritage more highly. Given these results, we consider it necessary to improve the initial training of teachers regarding existing heritage resources and to adapt teaching approaches in order to achieve a greater integration of heritage in history education.